TAFSSA stakeholder mapping: climate change adaptation policy and awareness in Bangladesh - Nur A Mahajabin Khan; Amitaksha Nag; Amjath-Babu, Tharayil Shereef; Krupnik, Timothy J. (TAFSSA, 2024)
Building on insights from the network mapping workshop, this analysis provides a comprehensive perspective on Bangladesh's climate adaptation network within the agrifood system, including the crop, livestock, and aquaculture sectors. The study presents a high-level understanding of the diverse stakeholders—organizations, institutions, and individuals from both the public and private sectors—who play critical roles in the stewardship of land and water resources and the promotion of climate adaptation strategies. The central research question guiding this mapping exercise is: Who are the primary organizations, institutions, and individuals in the public and private sectors that influence land and water resources conservation and climate change adaptation, with a focus on agricultural production, marketing and consumption systems in Bangladesh? Through this analysis, we aim to explain the interconnected patterns that emerge within the climate adaptation sub-system, identifying the pivotal drivers, persistent barriers, and systemic gaps that shape stakeholder interactions. These insights are critical to identifying actionable intervention points that can lead to meaningful and sustained transformation across the agrifood system, ultimately supporting enhanced resilience, nutritional outcomes, and adaptive capacity in the face of climate change.